Edukasi Pembuatan Buku Foto Destinasi Wisata Taman Tematik sebagai Media Promosi Pariwisata dalam Peningkatan Kunjungan Wisatawan di Kota Bandung: Education on Making Photo Books of Thematic Park Tourist Destinations as Tourism Promotion Media in Increasing Tourist Visits in Bandung City - Sumarna, Imam Budi; Riyadh, Achyar; Pratika, Nadiah Ayu (PengabdianMu: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2025)
Bandung is one of the tourist destinations that has many thematic parks that function as green open spaces as well as tourist attractions. However, the potential of these thematic parks has not been fully utilized as the main attraction for tourists. This research aims to promote thematic parks in Bandung City through tourism book media using photography as the main visual tool. This activity includes photographing the destination, compiling the tourism book, and disseminating the results through various platforms. The results of this activity show that photography-based tourism books are significantly able to attract tourists to visit thematic parks. The increase in tourist visits occurred as a result of the use of informative and attractive visual media.